2006
DOI: 10.1523/jneurosci.2181-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine and Sleep Homeostasis in the Basal Forebrain

Abstract: It is currently hypothesized that the drive to sleep is determined by the activity of the basal forebrain (BF) cholinergic neurons, which release adenosine (AD), perhaps because of increased metabolic activity associated with the neuronal discharge during waking, and the accumulating AD begins to inhibit these neurons so that sleep-active neurons can become active. This hypothesis grew from the observation that AD induces sleep and AD levels increase with wake in the basal forebrain, but surprisingly it still … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
114
3
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(122 citation statements)
references
References 59 publications
4
114
3
1
Order By: Relevance
“…Experiment 2: effects of SR141716A, URB597 or VDM-11 on neurochemical levels during the sleep rebound after 6 h of prolonged waking It is widely known that prolonged waking induces endogenous accumulation of several neurochemicals such as monoamines and purines whereas during the sleep rebound period, the contents of these molecules are decreased (Porkka-Heiskanen et al, 2000, 2002Lena et al, 2005;Blanco-Centurion et al, 2006;Monti and Jantos, 2008;Mohammed et al, 2011;Brown et al, 2012). Thus, the rationale of the following experiment was based to test whether SR141716A, URB597 or VDM-11 would modulate the extracellular contents of DA, NE, EP, 5-HT or AD after prolonged waking.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Experiment 2: effects of SR141716A, URB597 or VDM-11 on neurochemical levels during the sleep rebound after 6 h of prolonged waking It is widely known that prolonged waking induces endogenous accumulation of several neurochemicals such as monoamines and purines whereas during the sleep rebound period, the contents of these molecules are decreased (Porkka-Heiskanen et al, 2000, 2002Lena et al, 2005;Blanco-Centurion et al, 2006;Monti and Jantos, 2008;Mohammed et al, 2011;Brown et al, 2012). Thus, the rationale of the following experiment was based to test whether SR141716A, URB597 or VDM-11 would modulate the extracellular contents of DA, NE, EP, 5-HT or AD after prolonged waking.…”
Section: Resultsmentioning
confidence: 99%
“…Third, previous reports have shown that SR141716A enhances NE contents (Tzavara et al, 2001(Tzavara et al, , 2003Bedse et al, 2015). Fourth, there is evidence regarding the interaction between the CB 1 cannabinoid receptor and AD system Cerri et al, 2014) suggesting that SR141716A would be blocking the CB 1 cannabinoid receptors present in cholinergic neurons which are placed in basal forebrain, and they are presumably responsible for AD release (Blanco-Centurion et al, 2006;Huang et al, 2011).Taken together, it might be reasonable to consider that SR141716A or URB597 might activate the wake-related neurotransmission systems and control sleep homeostasis. Nevertheless, further studies are needed to clarify whether the endocannabinoid system interacts with wake-related components to control sleep homeostasis.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, the anatomical focus of these studies has been the BF rather than the cerebral cortex. Extracellular adenosine is known to accumulate in the BF with prolonged wakefulness (39,40). Prolonged waking activates inducible NOS in the BF which can cause adenosine release and thereby facilitate sleep (37).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, to obtain direct data on the sleepiness of experimental rats, a unique rodent multiple sleep latency test (MSLT) was used that contained features of the clinical MSLT and of procedures used in published animal studies (Shiromani et al, 1991;Veasey et al, 2004;Blanco-Centurion et al, 2006). The rodent MSLT was performed in the recovery period following 6 h SI with treadmill off at the beginning of the dark period (N=8); 6 h SI with treadmill off 3 h before the end of the light period (N=8); and 24 h SI (N=8).…”
Section: Rodent Multiple Sleep Latency Test Following Si Exposuresmentioning
confidence: 99%